Shopee PayLater Voucher pada Jual Beli Online dalam Perspektif Fikih Muamalah Kontemporer - Syamsiah Nur; Andi Dahmayanti; Miftahul Jannah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This study aims to determine the law on the use of Shopee PayLater Vouchers in buying and selling online in a review of contemporary muamalah fiqh. This research is a qualitative descriptive research or literature review using juridical and normative approaches. In analyzing the data, researchers used content analysis (content analysis). The results of this study are that Shopee PayLater Vouchers may not be used or claimed illegally, because the prize comes from an unlawful contract (riba qarḍ) Shopee PayLater. The implication of this research is that the community, especially Muslims who use this application, can know and understand the views of the Shari'a regarding Shopee PayLater Vouchers so that the Muslim community will always prioritize the precautionary principle that comes from knowledge in using these Vouchers.